The Effect of Running Speed on Cadence and Running Kinetics - Abbey Leacox; Lucy Fashingbauer; Thomas Ferguson; Anna Zajakowski; Brian Baum; Mark Reinking (International Journal of Sports Physical Therapy, 2025)
# Background